A simulated study on intermittent flame feature of mass fire in channel structure. (November 2022) - Zhang, Xi; Lai, Qing; Xiao, Huang; Li, Jie
Abstract: Compared with the intermittent thermal-flame behavior in ordinary building, the flame behavior may also occur in mass fire inside channel structures, accompanied by distinct thermal characteristics, which is rarely studied. This study used computational fluid dynamics with large eddy simulation to model the mass fires inside channel. The behavior characteristics of intermittent flame behavior under different fuels were identified. Results shown that when the fuel area reaches 1.08–1.98 m 2, flame behavior appears periodic motion, and the high temperature region, pressure distribution and ceiling temperature also show a trend of periodic variation. The movement direction of high temperature region is opposite to flame behavior. When the flame overflows from left portal, high temperature region appears near the right edge of fire source, and ceiling temperature shows a similar trend. As flame overflows from the portal, there is an obvious negative pressure region. The existence of negative pressure region is conducive to the air filling of portal on other side to support the fuel burning inside channel, and to maintain the flame behavior. This work can enrich the research of mass fire in channel structure to some extent.